Vehicle Location Privacy Protection Mechanism Based on Location and Velocity - Shaleesh, I.S. (Institute of Electrical and Electronics Engineers Inc., 2022)
Vehicular ad hoc networks (VANETs) are necessary to protect the lives of drivers by providing them with important information about the condition of the road. However, this type of network is vulnerable to eavesdropping due to the wireless medium of the spread of Beacons messages, which makes drivers worry about the possibility of being pursued through the network. Thus, protecting the privacy of vehicles is an urgent matter in VANETS environments. In this paper, a privacy protection system based on changing pseudonyms depending on the speed of the vehicle and its location inside or outside the predefined mix-zones is proposed. The simulation results show that the proposed strategy is an effective strategy to protect the location information of vehicle drivers. The proposed strategy outperforms existing strategies in terms of mean number tracker confusion, continuous tracking period, and maximum entropy. Â© 2022 IEEE.